Postconcussion symptoms and neuropsychological performance in athletes: a literature review - Ahmed, Z.; Benton, A. H.; Serra-Jovenich, M.; Toldi, J. P. (Current Sports Medicine Reports, 2023)
Neuropsychological assessment is a common part of concussion evaluation and plays an important role within the context of a comprehensive multidisciplinary approach to managing sports-related concussion. A literature review has shown an assortment of cognitive domains used for evaluation of PCS with their corresponding tests. This review focuses on the various cognitive domains following single or multiple TBIs in athletes. Decreases in memory, executive function, language, psychomotor function, and self-reported cognitive function reached statistical significance in concussed athletes versus controls. Length of time since onset of symptoms correlated with worse memory function in chronic concussion athletes and more headache symptoms correlated with a worse outcome as well. However, some treatments are shown to be beneficial for restoration of cognitive function. When analyzing these results, it is imperative to be cognizant of the bias in the current literature. Further well-designed studies are needed to replicate these findings in larger more diverse samples.